1995
DOI: 10.1093/hmg/4.10.1869
|View full text |Cite
|
Sign up to set email alerts
|

New polymorphic microsatellite markers place the haemochromatosis gene telomeric to D6S105

Abstract: The haemochromatosis gene (HFE) is linked to both HLA-A and D6S105 on the short arm of chromosome 6 but these markers are separated by approximately 2 Mb of DNA. Most chromosomes carrying HFE have a common haplotype which extends from HLA-A to D6S105 and includes HLA-F. To localise the gene more precisely we have examined 10 microsatellite markers extending over a genetic distance of approximately 5 cM from D6S265 (within 100 kb of HLA-A on the centromeric side) to D6S299 (telomeric). The order of markers is D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…These and subsequent studies of the strong linkage disequilibrium between HH and various markers in the MHC region all led to the expectation that a putative HH gene would lie within approximately 1 cM of the HLA-A locus (Gasparini et al 1993;Jazwinska et al 1993;Raha-Chowdhury et al 1995;Yaouanq et al 1994). While the HLA association has had profound implications both for the clinical diagnosis and cloning strategies of the HH gene, the possible biological significance of that association is only now becoming evident.…”
Section: Introductionmentioning
confidence: 99%
“…These and subsequent studies of the strong linkage disequilibrium between HH and various markers in the MHC region all led to the expectation that a putative HH gene would lie within approximately 1 cM of the HLA-A locus (Gasparini et al 1993;Jazwinska et al 1993;Raha-Chowdhury et al 1995;Yaouanq et al 1994). While the HLA association has had profound implications both for the clinical diagnosis and cloning strategies of the HH gene, the possible biological significance of that association is only now becoming evident.…”
Section: Introductionmentioning
confidence: 99%
“…The study of well-dechromosome 6 has been reported. [5][6][7] A candidate gene has fined atypical hemochromatosis families using genetic markbeen described (HFE), 4.5 Mb telomeric to HLA-A. 8 The use ers may increase our understanding of the sensitivity and the of haplotype analysis and the search for recombinations in specificity of genotyping in hemochromatosis.…”
mentioning
confidence: 99%
“…D6S306, D6S105, and D6S464, a group of wellcharacterized polymorphic markers, each with one allele in linkage disequilibrium with hemochromatosis (Raha-Chowdhury et al 1995), are located within the left third of y950h11, approximately at the center of the map. D6S1260 (Raha-Chowdhury et al 1995), one of the most telomeric markers reported to be tightly linked to hemochromatosis before the publication by Feder et al (1996), and D6S1016, a tetranucleotide-repeat marker thought to mark the telomeric boundary of the region of linkage disequilibrium with hemochromatosis (Seese et al 1996), are other noteworthy landmarks on this YAC.…”
Section: Yac-contig Mapmentioning
confidence: 99%
“…D6S1260 (Raha-Chowdhury et al 1995), one of the most telomeric markers reported to be tightly linked to hemochromatosis before the publication by Feder et al (1996), and D6S1016, a tetranucleotide-repeat marker thought to mark the telomeric boundary of the region of linkage disequilibrium with hemochromatosis (Seese et al 1996), are other noteworthy landmarks on this YAC. The hemochromatosis gene HLA-H is located in a map segment shared by clones y899g1 and y974a2.…”
Section: Yac-contig Mapmentioning
confidence: 99%